2013
DOI: 10.1088/2051-672x/2/1/014011
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of a vibration desensitized scanning white light interferometer

Abstract: Surface metrology instruments normally require thermal, seismic and acoustic isolation. Shop-floor metrology solutions offer reduced cost and process time. If they operate on the same principles as laboratory devices, an inherent sensitivity to vibration remains. This paper describes a methodology for evaluating 'environmental tolerance' and applying it to characterize a recently introduced 'environmentally tolerant' scanning white light interferometer (SWLI). Previously published measurements of replicated ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Typically, the as-measured morphological images have fixed pixels, e.g., 512 × 512 in AFM measurements. Thus, the pixels of a segmented sub-images is lower than that of an image attained by an actual measurement at the same L, which may partly decrease the credibility of Rq results, as many researchers [38][39][40] reported in their relevant studies. Therefore, questions may arise about the similarity and difference between the RSE and TR methods.…”
Section: Introductionmentioning
confidence: 94%
“…Typically, the as-measured morphological images have fixed pixels, e.g., 512 × 512 in AFM measurements. Thus, the pixels of a segmented sub-images is lower than that of an image attained by an actual measurement at the same L, which may partly decrease the credibility of Rq results, as many researchers [38][39][40] reported in their relevant studies. Therefore, questions may arise about the similarity and difference between the RSE and TR methods.…”
Section: Introductionmentioning
confidence: 94%
“…This could be done by measuring the vibrations with a sensor (e.g., accelerometer) and re-calculating (correcting) the Z values assigned to each image taken by the interferometer during its scan motion before surface data is reconstructed. Alternatively, the effectiveness of vibration-removal strategies originally developed for laboratory-based instruments can be tested [33,[38][39][40].…”
Section: Robot Arm Stability and Measurement-induced Vibrationsmentioning
confidence: 99%
“…This compact nature also enables robotic deployment, as demonstrated in [22][23][24][25] through the combined use of a laser line scanner (low resolution, for large area coverage) and a scanning interferometer (Heliotis H6, high resolution, for local high resolution measurements) mounted on a robot arm. While the performance evaluation of such high resolution instrumentation in a laboratory environment has been widely addressed [26][27][28][29][30][31][32][33], the application of these sensors in non-ideal, shop-floor applications, as well as in robotic deployment, clearly demonstrates the need for re-evaluating and extending performance standards [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This ripple pattern is an artificial artifact due to the limited environmental noise that exists during measurement. A detailed classification and quantitative study of the noise sources can be found in [33,34].…”
Section: Roughness Measurement Instruments and Parameter Studymentioning
confidence: 99%